Evaluasi Kesesuaian Resep Pasien Umum Rawat Jalan Terhadap Formularium di RS Umi Barokah Boyolali - Melandaria, Melandaria; Muslim, Ahmad Suriyadi; Mundriyastutik, Yayuk (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: Formularies are an excellent tool to improve the quality and efficiency of hospital treatment costs and can demonstrate the level of effectiveness in achieving therapeutic, economic and/or goals, administration. This study aims to find out the description of the suitability of writing outpatient general prescriptions with the formulary of Umi Barokah Boyolali Hospital for the September-November 2020 period. Method: This study used an observational research type. Data were collected retrospectively, namely by observing and evaluating prescription sheets taken from the general outpatient prescription sheet population for 3 months, namely September-November 2020. Sampling was carried out using systematic random sampling. The collection of data used is using secondary data. Secondary data is data obtained from all prescriptions that enter the Umi Barokah Boyolali Hospital Pharmacy Installation in the form of prescription archives, the number of prescriptions issued by each doctor and the drug list according to the formulary from September 2020 to November 2020. Result: It shows that in the September-November 2020 period the percentage of conformity of prescriptions based on prescription sheets was 99.42%, based on polyclinics 98.87%, based on drug items 99.72%. Conclusion: This study shows that the management of drugs installed in the Umi Barokah Boyolali hospital pharmacy is quite good because the majority of prescribed drugs are available, but when vieBackground: Formularies are an excellent tool to improve the quality and efficiency of hospital treatment costs and can demonstrate the level of effectiveness in achieving therapeutic, economic and/or goals, administration. This study aims to find out the description of the suitability of writing outpatient general prescriptions with the formulary of Umi Barokah Boyolali Hospital for the September-November 2020 period. Method: This study used an observational research type. Data were collected retrospectively, namely by observing and evaluating prescription sheets taken from the general outpatient prescription sheet population for 3 months, namely September-November 2020. Sampling was carried out using systematic random sampling. The collection of data used is using secondary data. Secondary data is data obtained from all prescriptions that enter the Umi Barokah Boyolali Hospital Pharmacy Installation in the form of prescription archives, the number of prescriptions issued by each doctor and the drug list according to the formulary from September 2020 to November 2020. Result: It shows that in the September-November 2020 period the percentage of conformity of prescriptions based on prescription sheets was 99.42%, based on polyclinics 98.87%, based on drug items 99.72%. Conclusion: This study shows that the management of drugs installed in the Umi Barokah Boyolali hospital pharmacy is quite good because the majority of prescribed drugs are available, but when viewed from the percentage of non-conformity of prescriptions to the formulary, it does not meet the minimum prescription service standard according to the formulary, namely 100%.wed from the percentage of non-conformity of prescriptions to the formulary, it does not meet the minimum prescription service standard according to the formulary, namely 100%.